Eukaryotic life without tQCUG: the role of Elongator-dependent tRNA modifications in Dictyostelium discoideum. Issue 14 (1st July 2020) - Schäck, Manfred A; Jablonski, Kim Philipp; Gräf, Stefan; Klassen, Roland; Schaffrath, Raffael; Kellner, Stefanie; Hammann, Christian
Abstract: In the Elongator-dependent modification pathway, chemical modifications are introduced at the wobble uridines at position 34 in transfer RNAs (tRNAs), which serve to optimize codon translation rates. Here, we show that this three-step modification pathway exists in Dictyostelium discoideum, model of the evolutionary superfamily Amoebozoa. Not only are previously established modifications observable by mass spectrometry in strains with the most conserved genes of each step deleted, but also additional modifications are detected, indicating a certain plasticity of the pathway in the amoeba. Unlike described for yeast, D. discoideum allows for an unconditional deletion of the single tQ CUG gene, as long as the Elongator-dependent modification pathway is intact. In gene deletion strains of the modification pathway, protein amounts are significantly reduced as shown by flow cytometry and Western blotting, using strains expressing different glutamine leader constructs fused to GFP. Most dramatic are these effects, when the tQ CUG gene is deleted, or Elp3, the catalytic component of the Elongator complex is missing. In addition, Elp3 is the most strongly conserved protein of the modification pathway, as our phylogenetic analysis reveals. The implications of this observation are discussed with respect to the evolutionary age of the components acting in the Elongator-dependent modification pathway.